CHILD AND YOUTH RESILIENCE AMONG RESIDENTS OF SELECTED ORPHANAGES IN KOLKATA, WEST BENGAL: AN EXPLORATORY CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction:  Resilience is a dynamic capability that helps children to survive challenges. Children and Youth living in underprivileged situations may have issues related to resilience, particularly in the phase of adverse childhood experiences. However, not much is known about it in Indian settings. The objective of this study was to assess the resilience levels among residents of selected orphanages in Kolkata, as well as the factors influencing their resilience. Methodology:  This descriptive study was conducted in four orphanages among 140 children aged 6-18 years in 2021. Data were collected by a predesigned, pretested, structured schedule on adverse childhood experiences using the ACE Questionnaire, and resilience was assessed using the Child & Youth Resilience Measure-28 questionnaire (CYRM-28 Questionnaire). Statistical analysis was done using IBM SPSS 16. Factors affecting child and youth resilience were put in a Multiple Linear Regression Model. Results: The mean of the resilience score (CYRM-28) was found 87.21±8.72. Age of the participants showed a significant negative correlation with ???????????????? Cyrm-28 Score (p-value 0.039, correlation coefficient -0.175). Multiple linear regression found that 14% of the variance of the dependent variable, i.e., ???????????????? Cyrm-28 value, can be explained by the model with predictors age, sex, education level, religion, type of orphan, type of orphanage, duration of staying in orphanage, and ACE score of the participants. ANOVA table indicated that the model is statistically significant (p-value 0.012) Conclusion: Understanding the factors that drive their resilience and educational aspirations is essential for developing effective interventions and support systems.